Fatigue assessment of as‐built and heat‐treated Inconel 718 specimens produced by additive manufacturing including notch effects. Issue 10 (29th July 2020) - Solberg, Klas; Wan, Di; Berto, Filippo
Abstract: The fatigue behaviour of notched and unnotched specimens produced by additively manufactured Inconel 718 were analysed in the as‐built and heat‐treated conditions. The surfaces display high roughness and defects acting as fatigue initiation sites. In the as‐built condition, fine subgrains were found, while in in the heat‐treated state, the subgrains were removed and the dislocation density recovered. SN‐curves are predicted based on tensile properties, hardness and defects obtained by fractography, using the area ‐method.